1994
DOI: 10.1128/iai.62.5.1749-1754.1994
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of fibrinolytic activities of Treponema denticola

Abstract: Several fibrinolytic activities of Treponema denticola, an oral spirochete associated with gingivitis and periodontal disease, were identified and characterized following phase partitioning with the nonionic detergent Triton X-114. The apparent molecular masses of the proteases ranged from 91 to 228 kDa when analyzed in sodium dodecyl sulfate-polyacrylamide gels containing fibrinogen as the protease substrate. A qualitative analysis of zymograms showed that the proteases were highly enriched in the detergent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 38 publications
4
28
0
1
Order By: Relevance
“…Examination of the proteolytic activity revealed that all strains degraded casein and showed trypsin-like or Arg-speci¢c protease activity and ¢brinogen was cleaved by nearly all strains tested. These results con¢rm the high peptidolytic capacity of treponemes described earlier [16,23]. T. vincentii, T. phagedenis, T. brennaborense, T. socranskii buccale and T. pectinovorum hydrolysed the substrate SAAPFNA but they did not degrade gelatin, indicating that they may possess an extracellular chymotrypsin-like proteinase exhibiting no gelatinase activity thus di¡ering from the surface-associated dentilisin.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Examination of the proteolytic activity revealed that all strains degraded casein and showed trypsin-like or Arg-speci¢c protease activity and ¢brinogen was cleaved by nearly all strains tested. These results con¢rm the high peptidolytic capacity of treponemes described earlier [16,23]. T. vincentii, T. phagedenis, T. brennaborense, T. socranskii buccale and T. pectinovorum hydrolysed the substrate SAAPFNA but they did not degrade gelatin, indicating that they may possess an extracellular chymotrypsin-like proteinase exhibiting no gelatinase activity thus di¡ering from the surface-associated dentilisin.…”
Section: Discussionsupporting
confidence: 83%
“…The ¢ltrate was centrifuged at 120 000Ug at 4³C for 2 h in a Beckmann ultracentrifuge. The precipitate contained the extracellular vesicles (fraction 2) as described by Rosen et al [23]. The protein content of the fractions was determined by the method of Lowry (DC Protein Assay; Bio-Rad).…”
Section: Examination Of Proteolytic Activitymentioning
confidence: 99%
“…Treponema denticola, which is also considered a pathogenic periodontal microorganism (Sela 2001), was shown to possess several highly proteolytic enzymes. These include a chymotrypsin-like protease, first described by Uitto et al (1988) and thoroughly studied by several others and named CTLP (Makinen et al 1995), T1 or phenylalanine protease (PAP) (Rosen et al 1994(Rosen et al , 1995, and Dentilisin (Ishihara et al 1996). It is of interest, therefore, that the results of the present study demonstrate that these enzymes are capable of degrading collagen membranes used in GTR.…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, both types of collagen membranes were cleaved by P. gingivalis cell membranes and the cell content associated proteases. P. gingivalis and T. denticola possess proteolytic activities associated with pathogenic properties related to the destruction of periodontal connective tissues, disruption of host defense mechanisms, and maintenance of the inflammatory response in the periodontal tissues (Makinen et al 1992(Makinen et al , 1994Rosen et al 1994Rosen et al , 1995Kadowaki et al 2000;Potempa et al 2000). Being one of the major causative agents of periodontal diseases, P. gingivalis produces large amounts of arginine-and lysine-specific cysteine proteinases in cell-associated and secretory forms, referred to as Arg-gingipain (Rgp) and Lysgingipain (kgp), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This organism exhibits a variety of potential virulence properties: coaggregation and synergy with other periodontal pathogenic bacteria (5); motility which enables it to penetrate and invade tissues (15); the ability to attach to host cells and tissues; cytotoxicity for epithelial cells, fibroblasts and endothelial cells (2,14,27); as well as expressing factors which interfere with neutrophile and lymphocyte functions (4,21,22). In addition, T. denticola also possesses a number of enzymes which have proteolytic, keratinolytic, fibrolytic and coUagenolytic activities (1,10,13,16,25). All of these attributes could contribute to the destruction of periodontal tissues.…”
mentioning
confidence: 99%